Pengaruh Work Life Balance terhadap Job Satisfaction Melalui Employee Engagement pada Karyawan Gen Z - Felisha Diensy Audillah; Dita Puruwita; Annisa Lutfia (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effect of work life balance on job satisfaction, mediated by employee engagement among Generation Z employees at PT Kereta Api Indonesia (Persero) Daop 1 Jakarta. The research background is based on the increasing number of Gen Z employees who have unique characteristics, such as a preference for work-life balance and meaningful engagement at work. The research method used is quantitative with a survey approach, in which data were collected through questionnaires distributed to Gen Z employees at PT KAI Daop 1 Jakarta. Data analysis was performed using Structural Equation Modeling (SEM). The results show that work life balance has a positive and significant effect on employee engagement and job satisfaction. Furthermore, employee engagement is proven to mediate the effect of work life balance on job satisfaction. The implications of this research highlight the importance for companies to pay attention to work-life balance and enhance employee engagement in order to improve job satisfaction, especially for Generation Z employees. These findings are expected to serve as a reference for companies in designing adaptive human resource management strategies that suit the characteristics of the younger generation in the workforce.